2021
DOI: 10.12714/egejfas.38.2.14
|View full text |Cite
|
Sign up to set email alerts
|

Effects of total replacement of dietary fish oil by vegetable oils on growth performance, nutritional quality and fatty acid profiles of rainbow trout (Oncorhynchus mykiss) at optimum and high temperature conditions

Abstract: The present study investigated the effects of total replacement of dietary fish oil by different vegetable oils on growth performance, nutritional quality and fatty acid profiles of rainbow trout (Oncorhynchus mykiss) at optimum and high temperature conditions. Five iso-nitrogenous and iso-lipidic diets including 100% fish oil and vegetable oils were prepared for rainbow trout fingerlings with an average weight of 11.27±0.01 g. After the fish were fed experimental diets for 9 weeks at the optimum temperature (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The study reported that the HSI values varied between 0.33 and 0.53, whereas the VSI values ranged from 11.06 to 12.23 (Keshavanath & Renuka, 1998). In a study conducted by Dernekbaşı (2012), the impact of varying ratios of canola oil added to the meal on HSI and VSI values in rainbow trout was investigated. The results indicated that HSI values ranged from 0.80% to 1.04%, whereas VSI values ranged from 10.03% to 11.99%.…”
Section: Discussionmentioning
confidence: 99%
“…The study reported that the HSI values varied between 0.33 and 0.53, whereas the VSI values ranged from 11.06 to 12.23 (Keshavanath & Renuka, 1998). In a study conducted by Dernekbaşı (2012), the impact of varying ratios of canola oil added to the meal on HSI and VSI values in rainbow trout was investigated. The results indicated that HSI values ranged from 0.80% to 1.04%, whereas VSI values ranged from 10.03% to 11.99%.…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, 328 articles were included in this research (Figure 1) and their detailed information is stored in Table S1. Among all the included articles, 73 were conducted on Oncorhynchus mykiss , 4,23,38–108 67 were about Salmo salar , 109–175 36 were for Oreochromis niloticus , 176–211 27 investigated Sparus aurata ,…”
Section: Methodsmentioning
confidence: 99%
“…Eventually, 328 articles were included in this research (Figure 1) and their detailed information is stored in Table S1. Among all the included articles, 73 were conducted on Oncorhynchus mykiss, 4,23, 67 were about Salmo salar, 36 were for Oreochromis niloticus, 27 investigated Sparus aurata, 21 used Dicentrarchus labrax, 14 focused on Epinephelus spp. [260][261][262][263][264][265][266][267][268][269][270][271][272][273] and the remaining 90 articles were on other species with lower report frequency.…”
Section: Literature Search and Selectionmentioning
confidence: 99%
See 1 more Smart Citation